1962
DOI: 10.1002/j.2050-0416.1962.tb01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Biogenesis of Essential Oil of Hops

Abstract: A scheme for the biosynthesis of the terpenoid constituents of the essential oil in ripening hop cones is put forward so far as current knowledge of their composition permits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1965
1965
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…It has been proposed that geranic acid is a derivative of geraniol and geranial, which are known as hop-derived flavor compounds, especially present in flavor hops. ,− ,, In previous studies, geranic acid was found in lemongrass, ginger, lemon oil, tomato, and grape, which are raw materials used for wine making. Methyl geranate, which is a methyl ester of geranic acid, has been reported as a compound derived from hop oil. ,,, Roberts et al assumed geranic acid to be a possible precursor of methyl geranate, which they first identified in hop oil . Peacock et al analyzed three commercial beers and detected geranic acid in only one of the beer samples at trace levels (1 μg/L) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that geranic acid is a derivative of geraniol and geranial, which are known as hop-derived flavor compounds, especially present in flavor hops. ,− ,, In previous studies, geranic acid was found in lemongrass, ginger, lemon oil, tomato, and grape, which are raw materials used for wine making. Methyl geranate, which is a methyl ester of geranic acid, has been reported as a compound derived from hop oil. ,,, Roberts et al assumed geranic acid to be a possible precursor of methyl geranate, which they first identified in hop oil . Peacock et al analyzed three commercial beers and detected geranic acid in only one of the beer samples at trace levels (1 μg/L) .…”
Section: Resultsmentioning
confidence: 99%
“…Methyl geranate, which is a methyl ester of geranic acid, has been reported as a compound derived from hop oil. 19,20,35,36 Roberts et al assumed geranic acid to be a possible precursor of methyl geranate, 36 which they first identified in hop oil. 35 Peacock et al analyzed three commercial beers and detected geranic acid in only one of the beer samples at trace levels (1 μg/L).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…from Žatec (Saaz) hops . Unlike β ‐myrcene and α ‐humulene and β ‐caryophyllene; β ‐farnesene is only found in certain hop varieties and usually in low amounts .…”
Section: Hop Essential Oilsmentioning
confidence: 99%
“…Since the boiling point of the non‐volatile fraction is higher than that of α ‐humulene in early hop oil examination, this portion was more challenging to analyse . However, these higher boiling substances are of interest to the brewer since these will most likely be retained in the wort after boiling and they may eventually find their way into the finished beer . The total oxygenated fraction is a complex mixture of alcohols, aldehydes, acids, ketones, epoxides and esters.…”
Section: Hop Essential Oilsmentioning
confidence: 99%
“…Both the metabolic pathways and morphological features of hop glandular trichomes have been studied. For example, Roberts and Stevens (1962) documented the biosynthetic pathway of the essential oils while Mori (1961) documented resin biosynthesis. Moreover, Oliveira and Pais (1988) reported morphological changes in glandular trichomes with development.…”
mentioning
confidence: 99%